1985
DOI: 10.1002/ajmg.1320200217
|View full text |Cite
|
Sign up to set email alerts
|

Dup(3)(p2→pter) in two families, including one infant with cyclopia

Abstract: We report on 2 unrelated cases of duplication of distal 3p due to balanced maternal translocation t(3;6)(p23;q27) and t(2;3)(p25;p23) respectively. One family was ascertained through the unbalanced offspring and the other through echographic examination of the balanced carrier mother. These cases confirm that dup(3)(p2----pter) results in a characteristic syndrome with distinctive facial appearance. In family 2 inspection of a photograph of a deceased sib was sufficient to conclude that he was affected. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…Cyclopia appears to be relatively common in trisomy 13 patients and has been reported in triploidy, trisomy 18, combined dup lq32-'qter and del7q34+qter, dup 3p21 +pter, del 18p and ring 18, and monosomy G [Cohen, 1966;Gimelli et al, 1985;Roach et al, 1975;Schinzel, 1984bSchinzel, , 1986Smart et al, 19861. As expected, many of the same chromosomal defects are associated with holoprosencephaly without cyclopia.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cyclopia appears to be relatively common in trisomy 13 patients and has been reported in triploidy, trisomy 18, combined dup lq32-'qter and del7q34+qter, dup 3p21 +pter, del 18p and ring 18, and monosomy G [Cohen, 1966;Gimelli et al, 1985;Roach et al, 1975;Schinzel, 1984bSchinzel, , 1986Smart et al, 19861. As expected, many of the same chromosomal defects are associated with holoprosencephaly without cyclopia.…”
Section: Discussionmentioning
confidence: 95%
“…Among approximately 20 cases observed [Pope et al, 1979;Suzumori et al, 1983;Gimelli, 1985, reviewed by Martin and Steinberg, 19831, most subjects had cardiac defects, gastrointestinal and urinary tract malformations, genital abnormalities, and craniofacial malformations, primarily of midline structures. Martin and Steinberg [ 19831 reported holoprosencephaly in one subject with dup(3)(p25-+pter).…”
Section: Introductionmentioning
confidence: 97%
“…Van Regemorter et al (1983) presented a case of HPE-PMA with der(10)t(3;10)(p21;q26)mat. Gimelli et al (1985) reported a case of cyclopia with der(2)t(2;3)(p25;p23)mat. Gillerot et al (1987) reported a case of cyclopia with der(10)t(3;10) (p12;q26)pat.…”
Section: Discussionmentioning
confidence: 98%
“…Vehi (1974), Gimelli et al (1985), Say et al (1976), Schinzel et al (1978, Surana et al (1977). Hersh et al (1980).…”
Section: Ballestamentioning
confidence: 99%
“…All 22 reported cases have been the result of infants receiving a derivative chromosome from a balanced rearrangement in a parent (Aarskog 1969, Ballesta & Vehi 1974, Buchinger et a1 1981, Charrow et al 1981, Francke 1978, Gimelli et al 1985, Hersh et al 1980, Monteiro de Pina Net0 & Ferrari 1980, McHugh et al 1971, Parloir et al 1979, Rethort et al 1972, Surana et al 1977, Say et al 1976, Schinzel et al 1978, Van Regemorter et al 1983, Yunis 1978. All 22 reported cases have been the result of infants receiving a derivative chromosome from a balanced rearrangement in a parent (Aarskog 1969, Ballesta & Vehi 1974, Buchinger et a1 1981, Charrow et al 1981, Francke 1978, Gimelli et al 1985, Hersh et al 1980, Monteiro de Pina Net0 & Ferrari 1980, McHugh et al 1971, Parloir et al 1979, Rethort et al 1972, Surana et al 1977, Say et al 1976, Schinzel et al 1978, Van Regemorter et al 1983, Yunis 1978.…”
mentioning
confidence: 99%